Sharia Cooperative Business Dispute Resolution in Indonesia Accepted Under the Guidelines of Sharia Economic Law - Nurjamil; Oyo Sunaryo; Atang Abdul Hakim (International Journal of Integrative Sciences, 2024)
The purpose of this study was to clarify how Sharia Economic Law is used to settle disputes involving cooperative businesses in Indonesia. This study uses a qualitative approach to the literature to investigate secondary data sources pertaining to Indonesian legislation and regulations pertaining to commercial conflict resolution. The findings demonstrated the crucial role that sharia cooperatives play in the Islamic economic system, particularly as a substitute finance source for the lower middle class. According to Indonesia's legal system, sharia business disputes, including those involving sharia cooperative businesses, can be settled through family mediation, legal proceedings in religious courts with absolute jurisdiction, arbitration, or alternative dispute resolution organizations like LAPSPI (banking), BMAI (insurance), BMDP (pension funds), BAPMI (capital market), BMPPVI (venture capital), and BAMPPI (guarantee). The establishment of LAPS Cooperatives that mesh well with the cooperative's spirit and have access to human resources with expertise in sharia-based cooperative business become crucial factors to take into consideration. Sharia cooperatives are seen as a unique type of business entity that operate member-based businesses that simultaneously hold two statuses (owner and user) and cooperative wealth owned by all cooperative members who run their businesses according to sharia principles